2013
DOI: 10.1177/0218492313492987
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450-isoenzyme 1A1 in susceptibility to tobacco-related lung cancer

Abstract: Carcinogens in smoke increase cytochrome P450 1A1 activity, which might be considered to play a role in cigarette smoking-induced lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…AHH, also known as cytochrome P4501A1, is a valuable biomarker for the early diagnosis of lung cancer [45]. The activity and expression of AHH are induced through the activation of the aryl hydrocarbon receptor (AhR) by PAHs [46].…”
Section: Discussionmentioning
confidence: 99%
“…AHH, also known as cytochrome P4501A1, is a valuable biomarker for the early diagnosis of lung cancer [45]. The activity and expression of AHH are induced through the activation of the aryl hydrocarbon receptor (AhR) by PAHs [46].…”
Section: Discussionmentioning
confidence: 99%
“…Lung cancer is the most frequently occurring malignant cancer and is the leading cause of cancer death worldwide [15,16]. Cigarette smoke contains more than 100 different mutagens and carcinogens and is the cause of approximately 90% of lung cancer cases [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Cigarette smoke contains more than 100 different mutagens and carcinogens and is the cause of approximately 90% of lung cancer cases [16,17]. Recently, it has been reported that TAMs can promote tumor progression, and an abundance of M2 macrophages have been found to infiltrate solid lung tumors, a characteristic that is associated with poor prognosis [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…The transformation of BaP into BPDE initiates the process of carcinogenesis by DNA adduct formation. [38][39][40] A significant reduction (p<0.0001) in the activity of AHH by DAS was observed in the serum as compared to BaP-exposed mice. The effect of DAS in the downregulation of CYP1A1 mRNA was reported in the lung and liver induced by methylcholanthrene.…”
Section: Dovepressmentioning
confidence: 87%